2022
DOI: 10.1371/journal.pone.0268991
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoeagenic E. coli occurrence and antimicrobial resistance of Extended Spectrum Beta-Lactamases isolated from diarrhoea patients attending health facilities in Accra, Ghana

Abstract: Introduction Diarrhoea accounts for high morbidity and mortality in children and adults worldwide. Extended Spectrum Beta-Lactamase-Producing Enterobacteriaceae (ESBL-PE) and Diarrhoeagenic Escherichia coli (DEC) contribute to prolonged hospitalization because of their resistance and virulence properties aiding in the spread of diarrhoeal disease and delayed treatment. Aim To determine DEC and the antimicrobial resistance of ESBL-PE isolated among diarrhoea patients attending two health facilities in Ghana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
4
10
2
Order By: Relevance
“…We also believed it was necessary to evaluate the barriers and facilitators of ASPs among hospital in Ghana to guide policies and strategies toward achieving the Ghana NAP goals to fight the rising rate of AMR and its impact on the healthcare system. [43][44][45][46] With respect to the 7 core elements of implementing sustainable ASPs. 15,21 leadership commitment emphasizes the necessity of a health facility having dedicated time, financial and human resources as well as prioritizing AMS activities to enhance appropriate antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…We also believed it was necessary to evaluate the barriers and facilitators of ASPs among hospital in Ghana to guide policies and strategies toward achieving the Ghana NAP goals to fight the rising rate of AMR and its impact on the healthcare system. [43][44][45][46] With respect to the 7 core elements of implementing sustainable ASPs. 15,21 leadership commitment emphasizes the necessity of a health facility having dedicated time, financial and human resources as well as prioritizing AMS activities to enhance appropriate antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…The result of LEfSe analysis further demonstrated that E. coli was enriched in HAG. E. coli has been described in many reports for their high resistance to antibiotics [38]. As a result, it is reasonable to deduce that low diversity of gut microbiota and high abundance of Bacteroidetes and Proteobacteria are a biomarker of long-term exposure to VAs and PVAs via the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of hospital patients with ESBL producing E. coli isolates have been reported in African countries such as South Africa, Uganda, and Tanzania [11][12][13]. Recent studies in a Ghanaian hospital reported that about 13.2% of diarrhoegenic E. coli isolates from patients were ESBL positive and cefotaxime resistant ESBL E. coli was found to be widely disseminated in Ghanaian hospitals [14][15][16].…”
Section: Introductionmentioning
confidence: 99%